343 Adversities, Distress, and Resilience in Hispanic Pregnant Women from Puerto Rico - Mary Rodríguez-Rabassa; Luisa I. Alvarado Domenech; Lillian Rivera; Karen G. Martínez-González; Sara Montalvo; Yolanda González; Roberto Burgos (Journal of Clinical and Translational Science)
Objectives/Goals: Pregnancy increases vulnerability to stress and mental health symptoms, particularly among Hispanic women in Puerto Rico (PR), a population with unique socioenvironmental adversities, such as poverty and natural disasters. This study examined the relationships between life adversities and psychological distress in this at-risk population. Methods/Study Population: Participants (n = 50) in this cross-sectional study were recruited from an obstetrician’s office in Southern PR. All participants provided written consent and completed the Adverse Life Experiences Scale (ALES, Cronbach’s alpha = 0.71) to identify lifelong adversities faced and the overall duration (chronicity). Measures of psychological distress included the Perinatal Anxiety Screening Scale (PASS, Cronbach’s alpha = 0.96), the Edinburg Postnatal Depression Scale (EDPS, Cronbach’s alpha = 0.87), the Perceived Stress Scale (PSS, Cronbach’s alpha = 0.79), and the Brief Resilience Scale (BRS, Cronbach’s alpha = 0.86). Descriptive and Spearman’s rho correlation analyses were conducted. Results/Anticipated Results: The mean age of the participants was 27.90 years (SD = 6.05), with most in the first trimester (66.0%). On average, participants reported 4.32 (SD = 3.1) out of 23 lifetime adversities. The most common adversities were natural disasters (60.0%), loss of a beloved (58.0%), and financial difficulties (38.0%). Nearly half (44.0%) experienced five or more adversities. A significant number of participants met the clinical threshold for anxiety (38.0%, PASS), depression risk (22.0%, EPDS), moderate-to-severe perceived stress (52.0%, PSS), and low resilience (24.0%, BRS). The overall duration of adversities was significantly associated with anxiety (rs = 0.50, p = 0.001) and stress (rs = 0.50, p = 0.007). Discussion/Significance of Impact: Hispanic pregnant women in PR face high levels of adversity and distress, which can negatively affect both maternal health and fetal development, influencing long-term child outcomes. Early identification and targeted interventions addressing adversities, can improve maternal mental health and child health-development outcomes.